Tingkat pencemaran air sungai Tondano di Kelurahan Ternate Baru Kota Manado - Lensun, Melky; Tumembouw, Sipriana S. (e-Journal BUDIDAYA PERAIRAN, 2013)
ABSTRACT The objective of this research was to detect the pollution level of Tondano River based on temperature, BOD, turbidity and dissolved oxygen parameters. Research was conducted at Ternate Baru Village, Manado City, from January to March 2013. Water sample was taken by purposive sampling at three stations at 08.00 AM, 11.00 AM, and 15.00 PM, each with two sampling points. Water quality was measured in situ for temperature and turbidity while dissolved oxygen and BOD were analysed in laboratory. Research results found temperature ranged from 270C-27,8 0C, turbiduty 37,9 - 150 NTU, dissolved oxygen 6,3 - 7,5 mg/L and BOD 15,5-44,5 mg/L. Based on Water Quality Standard Grade II PP No. 82, 2001, BOD and turbidity at Ternate Baru were high. It was concluded that water quality of Tondano River at Ternate Baru Village was categorized polluted. Keywords: water quality, pollution, Tondano River, Ternate Baru Village